Effect of Current Ratio, Return on Assets, and Return on Equity, on Price Earnings Ratio in Hospital Companies Listed on Indonesia Stock Exchange (Bei) in 2016-2021 - Syafira Monalisa (Journal of World Conference (JWC), 2022)
This study aims to analyze the Effect of Current Ratio, and Return On Assets, Return On Equity on the price Earning Ratio of Hospital Companies listed on the Indonesia Stock Exchange for the period 2016 - 2021. The samples used in this study were 5 Hospital Companies with the Purposive Sampling method. The analysis of this study used multiple linear regression analysis. The results showed that the Current Ratio partially had a significant effect on the Price Earning Ratio with the support of a positive direction. Return On Assets partially has a significant effect on the Price Earning Ratio with the support of the negative direction The Return on Equity has a significant effect on the Price Earning Ratio with the support of the positive direction .variable CR, ROA and ROE simultaneously (together) have a significant effect on PER.The next suggestion for researchers is to add other variables that were not studied in this study and use companies in other industrial sectors to obtain more varied results that can describe the overall what can affect the Price Earning Ratio.